Native valve infective endocarditis caused by Staphylococcus hominis in a patient hospitalized with Covid-19. Report of a case - Velez-Paez, Jorge L. (2020)
Covid-19 disease shows many different manifestations, from common symptoms affecting both the upper and lower respiratory tract, and also sensorial alterations such as anosmia or taste perversion. Heart valve thrombosis and subsequent endocarditis are extremely rare manifestations and they have been scarcely described within the context of Covid-19. We present a case of a patient that was positive for SARS-Cov-2, who developed Staphylococcus hominis bacteremia. Afterwards, he developed persistent fever, and after ruling out some differential diagnoses, a diagnosis of infective endocarditis affecting a native healthy aortic valve was made, using cardiac ultrasonography. This occurrence was considered to be hospital-acquired.